Retrieval-mediated directed forgetting in the item-method paradigm: the effect of semantic cues - Marevic, Ivan; Rummel, Jan (Psychological research, 2020)
Item-method directed forgetting is widely considered a storage phenomenon. However, by applying a multinomial model, which separates storage and retrieval effect components, Rummel et al. (J Exp Psychol Learn Mem Cogn 42(10):1526-1543, 2016) recently provided evidence that item-method directed forgetting effects are reflected by both storage and retrieval changes. The current investigation demonstrates that supposedly intentionally forgotten information can still be retrieved to some extent when semantic cuing facilitates retrieval of this information. Participants studied word pairs, with some pairs being followed by a “forget” and others by a “remember” instruction. A subset of items shared the same superordinate semantic category. In Experiment 1, a sub-portion of to-be-forgotten items was semantically related and less forgetting occurred selectively for these items when the category was reinstated during test. This finding was replicated and extended to reinstatement effects for to-be-remembered items in Experiment 2. The application of the storage-retrieval model confirmed that providing a category cue facilitates retrieval of to-be-forgotten as well as to-be-remembered information. The results are discussed in light of existing theories of directed forgetting.
Published online: 28 August 2018
Gesehen am 17.04.2020